Increasing the Protection of Human Trafficking Victims in Malaysia: (Memperkasakan Perlindungan Mangsa Pemerdagangan Manusia di Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2019)
Human trafficking is the fastest-growing transnational crime in the world, ahead of weapon and drug smuggling. This has led to the United Nations (UN) introducing the "3P" paradigm outlined in the Protocol to Prevent, Suppress, and Punish Trafficking in Persons Especially Women and Children. The "3P" paradigm is the main guideline in protecting human trafficking victims although Malaysia is not bound by this protocol as the country has not signed it. Nevertheless, Malaysia should implement steps to adhere to the protocol as it is one of the countries assessed in the TIP Reports issued since 2001 until now. Using the doctrinal approach, this article clarifies whether the international obligations must be met in Malaysia in order to ensure that victim rights are protected. This paper reveals that Malaysia has adopted a number of vital steps to comply with the international framework. Nonetheless, improvements are necessary to ensure more effective protection for trafficking victims using the "3R" approach-rescue, rehabilitation and reintegration.Keywords:human trafficking; "3P" paradigm; rights of victims; Malaysia, TIP